Learning at the museum: Factors influencing visit length. Issue 2 (March 2017) - Brida, Juan Gabriel; Nogare, Chiara Dalle; Scuderi, Raffaele
Museum attendance is often seen as a chance for visitors to learn and thus increase their cultural capital. However, a share of the visitors may decide to attend museums for reasons other than cultural capital accumulation. This article investigates whether learning process takes place also in the case of tourists whose main motivation for the visit is recreational. Different attitudes towards cultural consumption may have a role in explaining visit length, seen as a proxy for learning. We present an empirical analysis of the determinants of both willingness to stay and actual length of stay at a museum. Evidence is based on a survey of tourists visiting the Italian museum of Vittoriale. Generalized ordered logit under partial proportional odds assumption and Cox proportional hazard models are used to assess the role of the covariates. A set of economic, socio-demographic, trip-related and psychographic controls is tested, with particular emphasis on motivation.